Nauczanie misjologii w świecie chrześcijańskim i dla niego. Treść i metoda - Peter C. Phan; Klaudyna Longinus (Annales Missiologici Posnanienses, 2019)
The article begins with a brief deﬁ nition of „World Christianity” and elaborates three theses for conceiving the relationship between missiology and theology, the understanding and practice of Christian missions, and the teaching of missiology. I argue that outside missiology there is no theology. I also reject the separation between church history and missiology, the division between the historic churches of the West and the „mission lands” of the rest, and a narrow focus of the goal of Christian missions on conversion and church-planting. Finally, I recommend a shift from „church history” to „history of Christianity.”